Soil health management through conservation agriculture, agroforestry and natural farming systems - Syed Ali Abbas; Shagun Bali; Sadaf Rahman; Moksha Sharma; Amandeep Singh; Nahida Rehman Mir; Ravinder Singh; Nitika Kapoor; Renu Bhardwaj (Frontiers in Agronomy, 2026)
Globally, land degradation driven by the aggregate impacts of pollution and climate change poses a major challenge to sustainable agriculture, food security, and climate change adaptation. Approximately, one-third of the planet’s soil are classified as moderately to severely degraded due to erosion, loss of soil organic carbon, nutrient imbalance, salinization, and contamination by heavy metals, pesticides, and emerging pollutants. Climate change factors, such as rise in temperature, changes in precipitation, and climate extremes, which encompass physical, chemical and biological disturbances. In this context, Sustainable Farming Systems (SFS) emerge as crucial nature-based solution for restoring soil quality and enhancing climate resilience. This review critically integrates international and regional findings on soil health management through conservation agriculture (CA), agroforestry, and natural farming (NF), with particular emphasis on evaluating the effectiveness and suitability of these practices in improving the physical, chemical, and biological properties and indicators of soil health amid pollution and environmental changes. The findings clearly indicates that CA improves soil structural properties and water regime, the ability of agroforestry to improve the nutrient dynamics, biodiversity, and the long-term carbon sequestration; and NF improves soil detoxification processes and nutrient status through its own inherent inputs and minimizing reliance on external inputs. Collectively, these practices make significant contributions to beneficial ecosystem services including erosion control, carbon sequestration, and water resource efficiency. However, challenges related to scalability, manpower requirements, productivity gaps, and region-specific adoption constraints remain significant barriers. The review emphasizes the need a holistic and regionally tailored approach to facilitate the broader implementation of soil-centred strategies, thereby advancing Land Degradation Neutrality (LDN), enhanced climate change resilience, and support long-term sustainable agriculture practices.